The physiological differentiation along the midgut of Bombyx mori – inspirations from proteomics and gene expression patterns of the secreted proteins in the ectoperitrophic space. Issue 2 (18th December 2017) - Liu, L.; Qu, M.; Yang, J.; Yang, Q.
Abstract: The ectoperitrophic space (EcPS) between the insect midgut epithelial cells and the peritrophic matrix is an unexplored, clean resource for concentrated proteins secreted by the midgut epithelial cells, which offers an ideal opportunity to uncover the midgut functions. In this study, we used Bombyx mori as a model organism and performed comparative proteomic analyses of the secreted proteins in the EcPS at the feeding and wandering stages. A total of 372 proteins were identified from both stages and 70 proteins were predicted to be secreted. Amongst these proteins, 17 secreted digestive proteins were identified and their temporal and spatial transcriptional expression patterns demonstrated that all these proteins were up‐regulated at the feeding stage and differentially expressed in different parts of the midgut. Proteins with nutrient reservoir activity and defence activity were found to be up‐regulated at the wandering stage. This work is the first to show the presence of digestive enzymes in the EcPS of the insect midgut using a proteomic approach, which provides evidence that suggests a physiological functional differentiation of the insect midgut. It is very clear that the EcPS undergoes dynamic changes in its composition of proteins in response to the changing needs of the insect at different developmental stages.